2021
DOI: 10.1097/crd.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Disorders and Prognosis in Heart Failure: A Systematic Review

Abstract: Magnesium is an essential mineral for the human body and plays an important role in cardiovascular health. Hypomagnesaemia has been linked with increased cardiovascular mortality in heart failure; however, previous studies have yielded conflicting results. Even fewer studies have addressed the association between hypermagnesemia and prognosis in heart failure. The aim of the present systematic review was to investigate the association of serum magnesium levels with cardiovascular and all-cause mortality in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…However, hypomagnesemia causes mitochondrial dysfunction, oxidative stress, and inflammation [ 27 ], as discussed in the next section. Several studies have confirmed that hypomagnesemia is an independent risk factor for cardiovascular mortality, including sudden cardiac death [ 28 ]. Recent evidence suggests that magnesium plays a clinically significant role in vascular calcification and mortality in individuals with chronic kidney disease (CKD) [ 29 ].…”
Section: Hypomagnesemia and Cardiovascular Mortalitymentioning
confidence: 99%
“…However, hypomagnesemia causes mitochondrial dysfunction, oxidative stress, and inflammation [ 27 ], as discussed in the next section. Several studies have confirmed that hypomagnesemia is an independent risk factor for cardiovascular mortality, including sudden cardiac death [ 28 ]. Recent evidence suggests that magnesium plays a clinically significant role in vascular calcification and mortality in individuals with chronic kidney disease (CKD) [ 29 ].…”
Section: Hypomagnesemia and Cardiovascular Mortalitymentioning
confidence: 99%
“…Hypermagnesemia usually occurs when creatinine clearance decreases in renal dysfunction and in instances of excessive magnesium intake from dietary supplements or magnesium containing medication. Common causes of hypomagnesaemia include a magnesium-insufficient diet, reduced intestinal absorption of magnesium, and the use of diuretics which increases the urinary excretion of magnesium ( 12 ).…”
Section: Magnesium and Cardiac Arrestmentioning
confidence: 99%
“…According to the results, higher dietary magnesium intake and plasma concentrations corresponded to reduced risks of sudden cardiac death ( 19 ). A systematic review that included eight studies encompassing 13,539 individuals with heart failure, examined the relationship between levels of serum magnesium with cardiovascular and all-cause mortality ( 12 ). An independent risk factor for sudden cardiac death is hypomagnesemia.…”
Section: Magnesium and Cardiac Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium has also been crucial in regulating blood pressure, myocardial metabolism, cardiac contractility and excitability, and vascular tone 4,5 . Hypomagnesemia has been associated with elevated risk and adverse prognosis in individuals with diabetes, heart failure, coronary artery disease, and stroke [6][7][8][9][10] . Increased dietary magnesium intake reduced the risk of diabetes, stroke, metabolic syndrome, and hypertension [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%